BASIC APPROACHES TO MODERNIZATION OF EDUCATION FOR PERSONS WITH PECULIARITIES OF PSYCHOPHYSICAL DEVELOPMENT - Nadiya Ashytok (Vasyl Stefanyk Precarpathian National University, 2018)
Modernization of a society creates preconditions for the search of new approaches to the organization of teaching the children of special educational requirements, including the limited possibilities of the health. Integrated and inclusive forms of teaching are considered. In the article the essence and characteristics of inclusive education. The options for creating inclusive educational space in Ukraine are presented. Article reveals problems of modernization of an education system of children with the limited health capabilities, carried out in Ukraine. Models of inclusive education are considered. It is noted that an important condition for systemic reform of education of children with special needs is a comprehensive solution of problems related to the regulatory, organizational, financial, human, scientific and teaching of their training and education. The development strategy of the national education system should be formed adequately to the current integration and globalization, the requirements of the transition to a post-industrial civilization that will ensure sustainable development and the movement of Ukraine in the XXI century, National education system integration into the European and world educational space. The main development challenges of a society the foundations of inclusive education system as one of directions of social protection of invalids in Ukraine are identified, revealed and analyzed. To facilitate the implementation of this strategy is properly organized and implemented the practice of inclusive education, which Ukraine must coexist with general and special. Concluded significant difficulties and positive trends are emerging in the work with children with special adaptive capabilities. The opportunities and prospects for further development of education and social protection of children with disabilities in Ukraine are justified. Key words: inclusiveness, inclusive education, children with peculiarities of psychophysical development approaches to the organization of teaching children with special educational needs, problems of inclusive education.